2015
DOI: 10.1097/rli.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Magnetic Resonance Imaging for Local Tumor Staging in Patients With Primary Breast Cancer

Abstract: Integrated PET/MRI does not provide diagnostic advantages for local tumor staging of breast cancer patients in comparison to MRI alone. Positron emission tomography/MRI and MRI enable an improved determination of the local tumor extent in comparison to PET/CT, whereas all 3 imaging modalities offer a comparable diagnostic performance for the identification of axillary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 32 publications
(32 reference statements)
4
83
1
1
Order By: Relevance
“…The treatment plan was adjusted in all these patients. Considering cT-stage, a recent study by Grueneisen et al found that both PET/MRI and MRI enable better determination of breast tumor extent in comparison to PET/CT [26]. Similar to our results, PET/MRI did not provide diagnostic advantages for breast tumor staging compared to MRI alone.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The treatment plan was adjusted in all these patients. Considering cT-stage, a recent study by Grueneisen et al found that both PET/MRI and MRI enable better determination of breast tumor extent in comparison to PET/CT [26]. Similar to our results, PET/MRI did not provide diagnostic advantages for breast tumor staging compared to MRI alone.…”
Section: Discussionsupporting
confidence: 80%
“…PET/MRI, MRI and PET/ CT allowed for a correct positive or negative axillary nodal status in 86%, 80% and 88%, respectively (p > 0,05) [26]. Similar to our results, PET shows best results for axillary lymph node staging.…”
Section: Discussionsupporting
confidence: 79%
“…PET/CT was compared with PET/MRI in two studies totaling 85 patients (Table 4) (57,58). In the first, Pace et al confirmed the feasibility of PET/MRI in 36 breast cancer patients (57).…”
Section: Clinical Indications For Pet/mrimentioning
confidence: 99%
“…In the second study, on another 49 patients with 83 lesions, the modalities performed at a comparable level (58). However, T-stage was determined correctly in more patients with PET/MRI (41/50; 82%) than with PET/CT (34/50; 68% [ P < 0.05]).…”
Section: Clinical Indications For Pet/mrimentioning
confidence: 99%
“…For the N-staging, PET/MRI showed similar results of diagnostic accuracy with PET/CT (86 % vs. 88 %) and tended to be higher than MRI (80 %) [41]. Another study showed that PET/MRI provided lower sensitivity for primary tumor than MRI (77 % vs. 100 %), but higher specificity (100 % vs. 67 %).…”
Section: Breast Cancermentioning
confidence: 53%